Productivity, Head Quality, and Leaf Tipburn of Lettuce Plants as Affected by Foliar Spray with Calcium Chloride Under Different Rates of Nitrogen Fertilization - Elsayed, Abdalla A. A.; Bardisi, A.; Nawar, Dalia A. S.; Hassan, Asem A. S. A. (International Journal of Aquatic Research and Environmental Studies, 2026)
The present work was carried out at the private Farm to study the effect of different rates of nitrogen fertilization and foliar application with calcium chloride on dry weight, leaf pigment, mineral uptake by leaves, yield, and head quality (nitrate contents and leaf tipburn) of lettuce plants, which were grown at Al-Baalwa District, Ismailia Governorate, Egypt, during the two winter seasons of 2024/2025 and 2025/2026 under sandy soil conditions and using a drip irrigation system. This study included 12 treatments, which are combinations between 3 nitrogen rates (40, 60 and 80 kg N/fad.) and 4 levels of calcium chloride (control, CaCl₂ at 60, 120, and 180 mg/l). Fertilizing lettuce plants cv American grown in sandy soil during winter plantation with mineral nitrogen at 60 kg/ fed. and foliar spray with CaCl2 at 120 ppm increased total dry weight, dry matter in leaves, and total chlorophyll in leaf tissues at 75 days after planting as well as average head weight at harvesting time. Whereas, fertilizing with mineral nitrogen at 80 kg/ fed. and foliar spray with CaCl2 at 180 ppm increased head yield/ha., head diameter, and calcium contents in leaves.  Fertilizing with mineral nitrogen at 60 kg/ fed. and foliar spray with CaCl₂ at 180 ppm increased N, P and K uptake by leaves and reduced tipburn percentage in leaves. Mineral nitrogen at 40 kg /fed. and spraying with water was the best treatment for reducing nitrate concentration in leaves. Hectare=10000 m²=2.4 feddan.
Keywords: lettuce, nitrogen, CaCl₂, leaf pigments, yield and leaf tipburn.